2004
DOI: 10.1080/09515070410001665749
|View full text |Cite
|
Sign up to set email alerts
|

Student mental health. Part 2: the main study and reflection of significant issues

Abstract: The difficulties faced by students and the contributory stressors include developmental issues. A number of factors appear to be the precipitators of stress but despite various suggestions from researchers in other countries there is little evidence in the UK of a comprehensive plan to ameliorate student mental health. It was the aim of this study to identify the factors perceived as stressors by students, find the extzent to which the stressors affect the students and identify a possible remedial strategy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 3 publications
0
12
1
Order By: Relevance
“…Similarly, in a recent study on a Greek student sample, Papadioti and Kaltsouda (2008) found that female students tended to appear more depressed. Monk (2004) also found in her study of a UK student sample that females presented with more psychological difficulties, especially anxiety.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, in a recent study on a Greek student sample, Papadioti and Kaltsouda (2008) found that female students tended to appear more depressed. Monk (2004) also found in her study of a UK student sample that females presented with more psychological difficulties, especially anxiety.…”
Section: Discussionmentioning
confidence: 84%
“…In the literature, career issues as well as academic, relationship and financial difficulties have been found to be some of the major causes of stress for students (Grant 2002). Moreover, these variables are closely related to mental health issues and personal well-being (e.g., Andrews and Wilding 2004;Monk 2004;Roberts and Zelenyanski 2002).…”
mentioning
confidence: 98%
“…Mental health problems are one of the three major causes of the burden of disease in Australia (Begg et al, 2007). In addition, there is an increasing awareness of the elevated risk of mental health problems in university students (e.g., Eisenberg, Gollust, Golberstein, & Hefner, 2007;Monk, 2004). In an attempt to quantify the prevalence of depression and anxiety symptoms in university students in general practice, Shiels, Gabbay, and Exley (2008) mailed a screening instrument to a sample of students registered with a community general practice.…”
mentioning
confidence: 99%
“…However, a number of inductees have presented worsening levels of mental ill-health compared to young people in the general population (Association for University & College Counselling, 2006;Monk, 2004;Roberts & Zelenyanski, 2002;Royal College of Psychiatrists, 2006). Although this vulnerability can be partly explained by a recent expansion of the plurality of new learners amplified by widening participation policies (Connell, Barkham & Mellor-Clark, 2007), similar problems are reported within more prestigious and traditional universities (Bates, 2010;Paton, 2010).…”
Section: Introductionmentioning
confidence: 99%